EDUKASI DAN PRAKTIK HIDROPONIK BERBASIS KURIKULUM MERDEKA DI SDN 149 RUMBAI, PEKANBARU - Amalia, Amalia; Siswati, Latifa; Nizar, Rini (Universitas Mataram, 2025)
SDN 149 Rumbai - Pekanbaru faces limited understanding of modern agriculture and constraints in learning space. Hydroponic education and practice were chosen as innovative solutions based on the Merdeka Curriculum and P5. The program aims to enhance scientific literacy and environmental awareness through training and hands-on practice. It supports local food security and fosters environmental concern among students from an early age. Activities began with a needs assessment and installation of a simple hydroponic system. Theoretical and practical training was provided to both students and teachers. Evaluation was conducted through pre-tests, post-tests, and ongoing observation. Both students and teachers showed improved understanding of hydroponic concepts and practices. System installation was successfully implemented with active participation from the school community. The training was effective and enthusiastically received by participants. Environmental awareness campaigns were carried out through posters and student presentations. The program involved 34 participants from SDN 149 Rumbai - Pekanbaru. Activities included pre-tests, hydroponic system training and practice, and post-tests. Evaluation results indicated a significant improvement in participants’ understanding, especially in basic concepts and growing media. Active participation from students and teachers reflected high enthusiasm. The hydroponic system was successfully implemented and monitored through the initial harvest. This program proved effective as a learning medium and increased awareness of sustainable agriculture in the elementary school environment.